Biodiesel de babaçu, óleo residual e gordura suína: análise da estabilidade oxidativa e potencial corrosivo quando aditivados - Rangel, Nelly Vanessa Pérez (2020)
Biodiesel is a biodegradable fuel surrogate for diesel oil produced from different fatty materials. It is considered environmentally friendly because it is sulfur-free, non-toxic, and derived from renewable sources. However, the rapid biodiesel oxidation acts triggering a series of chemical reactions that affect its properties, representing one of the biggest challenges in the production and commercialization of biodiesel. The aim of the work was the production and characterization of biodiesel from babassu coconut oil (Attalea speciosa Mart.) (BOB), swine fat (BGS) and residual frying oil (BORF) by the methyl route. The samples were added with ionol, naugalube, and hydrogenated cardanol, at a dosage of 500 mg/kg, to assess oxidative stability and corrosive potential using the Rancimat accelerated oxidation test (EN 14112: 2003), and copper sheet immersion test at room temperature (28-30 °C) for 720 hours according to ASTM TM0169 / G31 - 12a (2010). The most severe corrosion occurred at biodiesels without additives. The additives reduced the corrosion rate by proportions of 8,2; 2,3, and 1,4 times for BOB, BORF, and BGS respectively. The naugalube (a synthetic compound) showed a positive effect on decreasing the corrosion rate and increasing the induction period (PI) in the three biodiesels. Hydrogenated cardanol showed pro-oxidant activity for BGS and BORF. The results suggest that the corrosion rate of copper can be reduced using ionol, naugalube, and hydrogenated cardanol, which are also used to retard the oxidation process.